Wilkie’s syndrome: Laparoscopic management – A case report with review of the literature (Indian Journal of Case Reports, 2022)
Superior mesenteric artery (SMA) syndrome also known as Wilkie’s Syndrome is a rare condition characterized by symptoms of small bowel obstruction. It is caused when the angle between the SMA and aorta, also known as the aorto-mesenteric angle, reduces to <25° which, in turn, causes the compression of the third part of the duodenum which traverses between the SMA and the aorta. We, herein, present the case of a 31-year-old female who was diagnosed to have Wilkie’s syndrome. Failing a trial of conservative management, she was ultimately definitively managed by surgery.